Tasa de aclimatación al cambio de temperatura de Mugil curema (Pisces: Mugilidae) de Venezuela - Segnini de Bravo, M. I. (1993)
We determined the time needed for Mugil curema juveniles to complete its acclimation to temperature changes. M. curema was acclimated during fifteen days at 24, 28, 30 and 34°C. Fish acclimated at 24°C were transferred suddenly to 3O"C and viceversa. Similarly it was done for fish acclimated at 28 and 34°C. We considered acclimation criterion, when thermal resistence of the fish was stabilized at the new temperature regime. The results showed that temperature tolerance of this species increased rapidly in 24 hours in a 6°C increase (24 to 30 and 28 to 34°C); however, it took 6-8 days to reach its acclimation level in decrease in temperature. Therefore, M. curema requires a shorter time to acclimate in an increase in temperature than in a decrease.